Fluoride in Drinking-water. - Fawell, J. (World Health Organization, 2006)
Fluoride is known to occur at elevated concentration in a number of parts of the world where it can be a significant cause of disease. The primary focus of this book is the prevention of adverse health effects from excessive levels of fluoride in drinking-water. The book fills the urgent need, identified for updating the WHO Guidelines for Drinking-water Quality, for information on the occurrence of fluoride, its health effects, ways of reducing excess levels and methods for analysis of fluoride in water. The draft document, produced by a working group of experts convened to consider protectio.